2009
DOI: 10.2174/092986709788453069
|View full text |Cite
|
Sign up to set email alerts
|

Recent Studies on Neural Tube Defects in Embryos of Diabetic Pregnancy: An Overview

Abstract: Maternal diabetes develops in 2-6% of total pregnancies, depending on geographical and ethnic background. About 10% of fetuses from diabetic pregnancy display congenital malformations in various organ systems including cardiovascular, gastrointestinal, genitourinary and neurological systems, among which the neural tube defects (NTDs) such as anencephaly, holoprosencephaly and syntelencephaly were more frequently demonstrated. Recent studies by the Diabetes Control and Complications Trial Research Group show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
41
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 0 publications
0
41
0
2
Order By: Relevance
“…8 Data also indicate that preexisting tissue damage and aberrant cell specialization due to hyperglycemia cannot be reversed even after normoglycemic levels are achieved during pregnancy. 9 Furthermore, exposure of the fetus to maternal hyperglycemia may have long-term impact on fetal cellular programming and therefore result in a greater predisposition to different diseases. 10 Epidemiologic evidence indicates that mothers with diabetes mellitus during pregnancy increase the risk of their offspring developing schizophrenia in adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…8 Data also indicate that preexisting tissue damage and aberrant cell specialization due to hyperglycemia cannot be reversed even after normoglycemic levels are achieved during pregnancy. 9 Furthermore, exposure of the fetus to maternal hyperglycemia may have long-term impact on fetal cellular programming and therefore result in a greater predisposition to different diseases. 10 Epidemiologic evidence indicates that mothers with diabetes mellitus during pregnancy increase the risk of their offspring developing schizophrenia in adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…To elucidate the negative impacts of gestational diabetes on cognitive functioning in the children, several researchers have been reported that diabetic mothers had offspring with significantly lower mean IQs than control infants [1][2][3][4][10][11][12][13]. Moreover, many of the developmental effects of gestational diabetes on the fetal CNS can be attributed to maternal hyperglycemia and fetal hyperglycemia/hyperinsulinemia [5,38,39].…”
Section: Discussionmentioning
confidence: 99%
“…abnormalities in offspring [1][2][3][4][5]. Several lines of studies have reported the wide spectrum of effects of gestational diabetes on the central nervous system (CNS) development and function including neurocognitive and neurodevelopmental defects [1][2][3][4][6][7][8][9].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…В од-ном из многочисленных исследований показано, что ком-плекс витаминов группы В (фолиевая кислота, витамины В 1 , В 2 , В 6 и В 12 ), витамин Е и минералы (кальций, железо, магний и цинк) редуцировали риск врожденной диафраг-мальной грыжи [64]. Употребление витаминов-антиокси-дантов (витамины С и Е) способствовало снижению ча-стоты ДНТ у детей женщин, больных сахарным диабетом [65]. В исследовании случай-контроль прием витамин-но-минеральных комплексов беременными женщинами полностью нивелировал риск развития тетрады Фалло и диспозиции крупных сосудов у детей [66].…”
unclassified